Assessing the Potential of Utilization and Storage Strategies for Post-Combustion CO2 Emissions Reduction - Armstrong, Katy; Styring, Peter (Frontiers in Energy Research, 2015)
The emissions reduction potential of three carbon dioxide handling strategies for post-combustion capture are considered. These are carbon capture and sequestration/storage (CCS), enhanced hydrocarbon recovery (EHR) and carbon dioxide utilization (CDU) to produce synthetic oil. This is performed using common and comparable boundary conditions including net CO2 sequestered based on equivalent boundary conditions. This is achieved using a 'cradle to grave approach' where the final destination and fate of any product is considered. The input boundary is pure CO2 that has been produced using a post-combustion capture process as this is common between all processes. The output boundary is the emissions resulting from any product produced with the assumption that the majority of the oil will go to combustion processes. We also consider the 'cradle to gate' approach where the ultimate fate of the oil is not considered as this is a boundary condition often applied to EHR processes. Results show that while CCS can make an impact on CO2 emissions, CDU will have a comparable effect whilst generating income while EHR will ultimately increase net emissions. The global capacity for CDU is also compared against CCS using data based on current and planned CCS projects. Analysis shows that current CDU represent a greater volume of capture than CCS processes and that this gap is likely to remain well beyond 2020 which is the limit of the CCS projects in the database.